In Search of Moderation of Islam Againts Extremism: A Promoting “Islam Pribumi” By Gus Dur - Muzayyin, Muzayyin; Kartika, Nadia Raifah Nawa; Habib, Habib (FIKRAH, 2021)
Indonesian religious expressions are facing an extraordinary challenge with the emergence of fundamentalist movements affiliated with number of Islamic transnationalist from Middle East, which is rigidly establishing the ideology of "purification" or as so called Islam Kaffah even if to be forced to the all nation. In this Case, Gus Dur presented another alternative religious pattern by promoting the idea of Islam Pribumi or “Islam Pribumi” which mean to respon and againts this scripturalist-fundamentalist movement. Islam Pribumi is intended to provide opportunities for the diversity of interpretations in term of practicing religious life (Islam) in each different region. Thus, Islam is no longer seen as a single, but rather compound. So there is no longer an assumption that Islam in the Middle East is the best representative of Islam. Therefore, this paper attempts to examine Gus Dur's thoughts on Islam Pribumi which is definitly inclusive, tolerant and peaceful Islamic culture, relflecting Islam as rahmatal lil alamin. It is also to offer a model of Islamic Moderation provided a solution in realizing global peace against conflicts between religions and politics that has occurred most recently in a Muslim-majority country like Syria, Afghanistan, Iraq, and Yemen.